FRI0123 Are there factors influencing the clinical vs ultrasound agreement in rheumatoid arthritis?. (23rd January 2014) - Le Boedec, M.; Jousse-Joulin, S.; Ferlet, J.-F.; Marhadour, T.; Chales, G.; Grange, L.; Hacquard-Bouder, C.; Loeuille, D.; Sellam, J.; Albert, J.-D.; Bentin, J.; Chary-Valckenaere, I.; et al.
Abstract : Objectives: To evaluate agreement between clinical (C) and ultrasound (US) assessment of synovitis (B, D and B+D mode) in active rheumatoid arthritis (RA) before and after treatment by antiTNF, and then to study factors associated with a good agreement. Methods: 76 active (necessitating an anti-TNF therapy) RA (1987 ACR criteria) patients have been included in a prospective, 2 year follow-up multicenter cohort. For each patient, 38 joints were evaluated (2 wrists, 2 elbows, 2 shoulders, 2 knees, 10 MCP, 10 PIP, 10 MTP). Synovitis grade was collected at baseline using a semi-quantitative variable for both the physical examination (from 0=definitively no synovitis to 3=yes obvious and important), US Grey Scale (GS) (from 0=absence of synovial thickening to 3=marked synovial thickening) and US Power Doppler (PD) (from 0=absence of signal, no intra-articular flow to 3=marked signal in more than half of the synovial area. The kappa coefficient was determined to evaluate the reliability of categorical variables (synovitis if grade ≥1). Factors associated with a good agreement were evaluated using both uni and multivariate analysis (all items statistically significant in univariate model and not correlated with other items were included). Results: Concordance before anti TNF between C and US assessment (kappa -0.08 to 0.51) as well as agreement between B and D mode (0.30 to 0.67) were variable according to the evaluated joint site. C and US agreement was particularly low on MTP and shoulders (kappa<0.3); they were excluded for the evaluation of factors associated with good C-US agreement. Practically all synovitis detected using D mode were also detected using B mode which was more sensible. Factors associated with good C-US agreement according to the multivariate analysis before anti TNF were: 1] B mode: low DAS 28, high physician VAS and positivity of rheumatoid factors (RF) 2] D mode: no semi recent evolution of RA (2-5 years), moderate activity of RA (DAS 3.2-5.1), age between 40-50 yrs and female sex. After anti TNF they were: 1] B mode: joint site (knees, elbows, MCP 4 and 5, IPP 2 to 5), male sex, low BMI, no semi recent evolution of RA (2-5 years), moderate disability on HAQ and low DAS 28. 2] D mode: joint site (knees, elbows, MCP 4 and 5, IPP 1 to 5), low BMI, recent evolution of RA, moderate disability on HAQ, low DAS 28, low physician VAS and positivity of rheumatoid factors (RF). Conclusions: Agreement between C and US assessment is joint site dependent. C assessment underestimates particularly MTP and shoulder synovitis. Factors associated to a good agreement on the other sites are numerous and variable according to US mode (factors associated to C-US mode B and D good agreement are different) and treatment (joint site, HAQ, low BMI are associated to a good C-US agreement after but not before TNF therapy). Disclosure of Interest: None Declared